Biology of fishes - Bone, Q.; Moore, Richard H., 1945- (New York : Taylor & Francis, 2008)
This is an ideal textbook for students of fish biology and any of the branches of aquatic biology. Given its combination of breadth and detail, the book also provides a manageable review of fish biology for experienced biologists.
Description based on print version record.
Includes bibliographical references and indexes.
Keywords: Fishes; Fishes -- Physiology; Fishes -- Anatomy; Fishes -- Ecology; Electronic books